Fabrication and Characterisation of Azithromycin-Loaded Ethosomes as an Advanced Vesicular Carriers for Acne Therapy - Patil, Abishek Kumar Anant; Halagali, Prashant Shivanand; Koli, Rahul Ramesh; Shirkoli, Nisha; Japti, Veerkumar Prakash; Sutar, Kishori Prasanna (Indian Journal of Pharmaceutical Education and Research)
Aim: This study is aimed to design and evaluate azithromycin-loaded ethosomes as an innovative approach to address the limitations of conventional azithromycin topical dosage forms in the treatment of acne. Materials and Methods: Azithromycin-loaded ethosomes were prepared using the ethanol injection method. Their physicochemical properties were evaluated using techniques like FTIR, DSC, particle size analysis and drug content determination. The formulation was optimized using a central composite design to achieve optimal drug entrapment and release. Results: The optimized formulation, Azithromycin loaded ethosomes 04 (AZT-ETH 04), demonstrated excellent performance, with an entrapment efficiency of 95.56±2.21%, drug content of 81.18±2.00%, a polydispersity index of 0.31±0.01, a zeta potential of -26.21 mV and a particle size of 174.73±2.16 nm. Aloe vera juice was employed as the base for an ethosomal gel incorporating Azithromycin loaded ethosomes 04 (AZT-ETH 04), formulated using Carbopol 934 (1.8%) as the gelling agent. The ethosomal gel exhibited desirable properties, including a pH of 6.53±0.15, viscosity of 756±3.27 cPs, spreadability of 3±0.19 g cm/s and an impressive drug release of 89.18±1.01% over 9 hr. Conclusion: The optimized azithromycin-loaded ethosomes exhibited superior physicochemical properties, including high drug entrapment and small particle size. The ethosomal gel, formulated with aloe vera juice and Carbopol 934, demonstrated desirable properties like optimal pH, viscosity and spreadability. It also exhibited a sustained drug release profile and potent antibacterial activity, making it a promising topical delivery system for acne treatment.
Keywords: Azithromycin; Central-Composite Design; Design of experiment; Ethosomes; P. Acne.